2020
DOI: 10.1371/journal.pone.0235701
|View full text |Cite
|
Sign up to set email alerts
|

Significant intraocular pressure associated with open-angle glaucoma: Korea National Health and Nutrition Examination Survey 2010-2011

Abstract: Objectives To investigate significant intraocular pressure (IOP) levels associated with the risk of openangle glaucoma (OAG) in the treatment-naïve Korean population. Methods Participants �20 years of age in Korea National Health and Nutrition Examination Survey 2010-2011 were divided into two groups, those with higher and lower IOP values, compared with the reference IOP value. We compared the risk of OAG in each group using regression analyses. The IOP value that yielded the highest statistical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These observations suggest a potential link between UA, glaucoma development, and oxidative stress in the pathogenesis of PACG. [22][23][24]…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest a potential link between UA, glaucoma development, and oxidative stress in the pathogenesis of PACG. [22][23][24]…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate adjusted models showed that men without glaucoma who drank alcohol over 2 times per month exhibited significant increases in IOP according to amount of alcohol consumed and that men who drank alcohol over 2 times per week were significantly more likely to have high IOP (≥18 mmHg). In this study, we defined 18 mmHg as a high IOP value because it has been associated with the development of OAG [ 29 , 30 ]. In subjects with glaucoma, the IOPs of men who did not consume alcohol at all were higher than among the total sample, while we observed significant increases in IOP among women glaucoma subjects who drank alcohol over 4 times per week.…”
Section: Discussionmentioning
confidence: 99%
“…IOP, a major causal risk factor for developing glaucoma and currently the only modifiable glaucoma risk factor, is affected by menopause (Vajaranant and Pasquale 2012 ; Altintas et al 2004 ; Vajaranant et al 2016 ; Panchami and S. R. et al. 2013 ; Kim et al 2020 ). Ocular hypertension (OHT), defined as an IOP > 21 mmHg, is associated with an increased risk of developing glaucoma compared to the normotensive population (IOP of 10–21 mmHg) (Morrison and Pollack 2003 ; Sommer et al 1991 ; Sugiyama 2012 ).…”
Section: Menopause and Glaucoma Riskmentioning
confidence: 99%